A STUDY ON QUALITY OF WORK LIFE OF HAWKERS IN TENKASI (International Journal of Food and Nutritional Sciences, 2022)
A hawker sells/offers varied products and services to the public through push cart, cycles or through a temporary space. This has been referred by the Government of India as Urban hawkers representing the basic urban poor who form a vital part of Indian economy. From selling fruits and vegetables to hosiery goods, a large part of Indian household relies on their services for meeting their needs. Tenkasi being the bustling agriculture market of the nation is also a hub for these small entrepreneurs. This occupation is a critical factor to the already poor employment statistics. Through this effort, the researchers aim to understand the problems face by these hawkers and the quality of work life. Their significant contribution is seldomnly highlighted by research studies and rarely their plight is exposed. The researchers focus on the hawkers and their demographics and therefore aim to identify the issues pertaining to their development. As the vision of great leaders is considered, economic development should not be at the cost of these leading to threat to the major fabric of social economy of the urban poor. If they exist only then the urban poor feel that they do have chance of having basic products suiting their requirements. Planned rehabilitated is a welcome step but the bustling marketplace of new migrants looking for sustenance cannot be fulfilled fully.